Shorted Patch Antenna With Multi Slots for a UHF RFID Tag Attached to a Metallic Object - Minh-Tan Nguyen; Yi-Fang Lin; Chien-Hung Chen; Chun-Hsien Chang; Hua-Ming Chen (IEEE Access, 2021)
This study developed a miniature tag antenna attached to a backing metal for ultrahigh-frequency radio frequency identification (RFID) applications. The impedance of this antenna can be easily controlled at the desired fixed frequency by using different mechanisms and was not considerably affected by backing metal size. This antenna comprises a radiating patch with double I-shaped slots and a ground layer shorted to a narrow inductive plate. Loading a closed slot in the center of the patch and the open slits enabled flexible frequency tuning to match the complex impedance of the microchip used. This tag antenna has a low profile of $28.02× 25.02×2.61$ mm3 ( $0.086× 0.076× 0.0079\,\,λ _{0}^{3}$ ), and it provides a high power transmission coefficient of 99.74%, realized gain of −2.3 dB, and a reading distance of 8.1 m when it is located at the center of a metallic plate of size $250×250$ mm2. The operational frequency of the proposed antenna was designed to reside the frequency bands for North and South America (860–960 and 902–928 MHz, respectively). Measurements of the antenna prototype proved that the experimental results agreed with the simulated data.